ADVOKASI GERAKAN PEREMPUAN DI EROPA DALAM INSTITUSIONALISASI NORMA KESETARAAN GENDER INTERNASIONAL (European Women’s Movement Advocacy in Institutionalizing the Global Gender Equality Norm) - Dewi Setiyaningsih (HI 16 UMY 132, 2016)
This research illmunates the strugle of women’s movement in putting the gender equality norm into international politics. From the constructivism paradigm, gender equality norm can be seen as something that created by agent. Using the concept of Life Cycle of Norm, this reseaRch discover the global gender equality norm grew through three stages, its emergence process, cascade process and internalization process. This reseaRch focuses on the cascade process, where the gender equality norm became institutionalized. It exemines the strategy of women’s movement in affecting the global agenda setting untill it emerged global gender equality norm, it marked by the forming of global gender instruments and its effect on domestic policy.